Chemerin activates fibroblast-like synoviocytes in patients with rheumatoid arthritis - Kaneko, Kayoko (BioMed Central, 2011)
INTRODUCTION: Chemerin is a chemotactic agonist identified as a ligand for ChemR23 that is expressed on macrophages and dendritic cells (DCs). In this study, we analyzed the expression of chemerin and ChemR23 in the synovium of rheumatoid arthritis (RA) patients and the stimulatory effects of chemerin on fibroblast-like synoviocytes (FLSs) from RA patients. METHODS: Chemerin and ChemR23 expression in the RA synovium was ascertained by immunohistochemistry and Western blot analysis. Chemerin expression on cultured FLSs was analyzed by ELISA. ChemR23 expression on FLSs was determined by immunocytochemistry and Western blot analysis. Cytokine production from FLSs was measured by ELISA. FLS cell motility was evaluated by utilizing a scrape motility assay. We also examined the stimulating effect of chemerin on the phosphorylation of mitogen-activated protein kinase (MAPK), p44/42 mitogen-activated protein kinase (ERK1/2), p38MAPK, c-Jun N-terminal kinase (JNK)1/2 and Akt, as well as on the degradation of regulator of NF-κB (IκBα) in FLSs, by Western blot analysis. RESULTS: Chemerin was expressed on endothelial cells and synovial lining and sublining cells. ChemR23 was expressed on macrophages, immature DCs and FLSs and a few mature DCs in the RA synovium. Chemerin and ChemR23 were highly expressed in the RA synovium compared with osteoarthritis. Chemerin and ChemR23 were expressed on unstimulated FLSs. TNF-α and IFN-γ upregulated chemerin production. Chemerin enhanced the production of IL-6, chemokine (C-C motif) ligand 2 and matrix metalloproteinase 3 by FLSs, as well as increasing FLS motility. The stimulatory effects of chemerin on FLSs were mediated by activation of ERK1/2, p38MAPK and Akt, but not by JNK1/2. Degradation of IκB in FLSs was not promoted by chemerin stimulation. Inhibition of the ERK1/2, p38MAPK and Akt signaling pathways significantly suppressed chemerin-induced IL-6 production. Moreover, blockade of the p38MAPK and Akt pathways, but not the ERK1/2 pathway, inhibited chemerin-enhanced cell motility. CONCLUSIONS: The interaction of chemerin and ChemR23 may play an important role in the pathogenesis of RA through the activation of FLSs.